Model of An Increasing Quality of Nursing Service (Satisfaction) for Poor Patient in Public Health Center Indonesia - Nursalam Nursalam; Pratiwi Pratiwi; Laily Hidayati (Universitas Airlangga, 2013)
Introduction: Nursing care Quality in a health center was one form of services that had to be considered and adjusted based on customer perception. The purpose of this study was to analyse the model of quality nursing service based on the customer perspective using the theory of Service Quality (SERVQUAL) for Poor patient in Public Health Center in Indonesia. Method: The study was a descriptive survey design. The respondents were all patients at Puskesmas Ngletih- Kediri. There were 46 respondents who had been chosen by simple random sampling. Research variables were the recommendation of others, customer needs, past experiences and the quality of nursing care. Data were collected using a questionnaire that was modified from the theory of service quality by Parasuraman and analyzed using binary logistic regression test with a significance level of p < 0.05.Results: The results showed that the recommendation from others (p = 0.011), customer requirements (p = 0.033), and past experiences (p = 0.009) were related to the quality of nursing care. Past experience variables had the greatest chance to determine the quality of nursing care at Puskesmas Ngletih to be good. Three variables had a chance of 78.26% to form a customer’s perception of good service quality all at once.Discussion: It can be concluded that thecustomers get the recommendation of others, can fulfill their needs, and have good experiences because of a good nursing care quality in the health center. On the other hand, if the customers get bad experiences and their needs are not met, they will not recommend to others to use the services of nursing services at the health center and customers’ perceptionabout the good quality of nursing care will not be formed.